Pelatihan Pemanfaatan Alternatif Pengelolaan Sampah Menjadi Ekoenzim Untuk Mendukung Ekonomi Kreatif Masyarakat - Endang Junita Sinaga; Adiani Hulu; Emmi Silvia Herlina; Lasmaria Nami Simanungkalit (LPPI UMN AL WASHLIYAH, 2026)
Household organic waste management in rural areas remains predominantly reliant on the conventional collect, transport, and dispose system, which contributes to the increasing volume of waste in landfills and exacerbates environmental pollution. The low level of circular economy implementation highlights the need for community-based innovations. The community service activity was conducted in Situmeang Hasundutan Village, Pintu Bosi, using a participatory approach. The methods comprised dissemination of circular economy principles, training in eco-enzyme production at a 1:3:10 ratio (sugar, organic waste, and water), practical sessions, and guided monitoring of the fermentation process. Evaluation was conducted through observation and participant feedback. The results indicate enhanced community knowledge and practical skills in the independent processing of organic waste. Participants were able to produce eco-enzymes with a successful initial fermentation process and recognized their potential use as liquid fertilizer and natural cleaning products. The program effectively reduced organic waste volume and generated opportunities for eco-friendly product-based enterprises, contributing to environmental sustainability and the development of the village's creative economy.